Gender and Corruption in Developing Countries - Regmi, Udaya Raj (Administration and Management Review, 2009)
This paper seeks to analyze the relationship between gender and Corruption in developing countries. Gender is the burning issue which has bilateral relationship with corruption. Owing to rampant corruption, women are hardly hit by poverty, illiteracy, poor health, violence, and sexual harassment in governmental and non-governmental Organizations. Trafficking in women is increasing throughout the world. Higher representation of women in parliament, ministerial posts, government bureaucracy, labor force, and legal and judicial system help mitigate the problem of corruption in these countries because of their widely accepted trustworthiness, higher standards of ethical behavior, more concerned with the common good, less criminal than their male counterpart, less involved in corruption, less tolerant of dishonesty and illegal conducts than men.Administration and Management Review Vol. 20, No. 1, January 2008, Page 1-16